HPM for Solving the Time-fractional Coupled Burgers Equations - Abu Alnaja, Khadijah (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, the homotopy perturbation method is implemented to derive the explicit approximate solutions for the time-fractional coupled Burger’s equations. The including fractional derivative is in the Caputo sense. Special attention is given to prove the convergence of the method. The results are compared with those obtained by the exact at special cases of the fractional derivatives. The results reveal that the proposed method is very effective and simple.